What is desired in future studies of endoscopic balloon dilation for patients with Crohn's disease?. Issue 4 (22nd March 2022) - Yano, Tomonori; Kawarai Lefor, Alan; Yamamoto, Hironori
Abstract : This Editorial refers to the article by T. Takeda et al., p 517‐525 of this issue DEN 34:3 .